Distributed strain measurement and possible breakage detection of optical-fiber-embedded composite structure using slope-assisted Brillouin optical correlation-domain reflectometry. (7th June 2018) - Lee, Heeyoung; Ochi, Yutaka; Matsui, Takahiro; Matsumoto, Yukihiro; Tanaka, Yosuke; Nakamura, Hitoshi; Mizuno, Yosuke; Nakamura, Kentaro
Abstract: Slope-assisted Brillouin optical correlation-domain reflectometry (SA-BOCDR) is a recently developed structural health monitoring technique for measurements of strain, temperature, and loss distributions along optical fibers. Although the basic operational principle of this method has been clarified, no measurements using optical fibers embedded in actual structures have been reported. As a first step towards such practical applications, in this study, we present an example of an SA-BOCDR-based diagnosis using a composite structure with carbon fiber-reinforced plastics. The system's output agrees well with the actual strain distributions. We were also able to detect the breakage of the embedded fiber, thus demonstrating the promise of SA-BOCDR for practical applications.